Ni ange ni bete: Roman / Andre Maurois - Maurois Andre (Le Livre de Poche, 1964)
Экземпляры: ИН (20030506) / Инвентарный номер: ин38207 / Цена: 15.00 / Сис.шифр: И(Фр) / Авт.знак: M 41 / ГРНТИ: 17 / ББК: 84(4/8)